Teriflunomide for the Treatment of Relapsing Multiple Sclerosis: A Review of Clinical Data. (September 2013) - Brunetti, Luigi; Wagner, Mary L.; Maroney, Megan; Ryan, Melody
Objective: To review the pharmacology and clinical data for teriflunomide in relapsing multiple sclerosis (MS).Data Sources: A literature search from 1966 to May 2013 using PubMed/MEDLINE, Web of Science, International Pharmaceutical Abstracts, Academic Search Premiere, Science Citation Index, and the national clinical trials registry was performed using the terms teriflunomide, HMR1726, and A771726. All articles containing human clinical trial data and relevant pharmacologic information were reviewed.Study Selection/Data Extraction: Phase 2 and phase 3 clinical trials for teriflunomide were evaluated. All peer-reviewed articles with clinically relevant information were reviewed. Priority for inclusion was placed on randomized controlled trials.Data Synthesis: Three phase 2 and three phase 3 clinical trials have evaluated teriflunomide as monotherapy or as adjunctive therapy in approximately 3000 patients with relapsing forms of MS. The phase 3 studies used annualized relapse rate, magnetic resonance imaging changes, and Expanded Disability Status Scale scores as outcome measures. One additional Phase 3 clinical study is ongoing. The annualized relapse rates and magnetic resonance imaging findings were improved compared to those with placebo and similar to or improved compared with those with subcutaneously administered interferon-β-1a 44 µg thrice weekly. Durability of response is supported by open-label extension studies. Common adverse events include increased liver function enzymes, alopecia, diarrhea, influenza, nausea, and paresthesias. Treatment discontinuation was not common and occurred in approximately 10% of patients in phase 3 studies.Conclusions: Teriflunomide is an effective and safe oral treatment option for relapsing MS. It can be used as monotherapy or added to an interferon or glatiramer acetate. It reduces the rate of relapse and may slow disease progression. The advantages of this drug are the convenience of oral administration and good tolerability. The disadvantage is the lack of long-term safety data and data about the benefit of combination therapy.